Review of Localization Approaches in Wireless Sensor Networks - Dipak Wajgi, Dr. Ujwalla Gawande, Dr. Rakhi Wajgi (International Journal of Advanced Science and Technology, 2020)
Wireless sensor network is increasingly becoming a source of interest for many researchers for conducting their research in the areas where human being cannot reach. The importance of the wireless sensor network in the areas like geographical studies has attracted the world. The localization in such research is very important as far as the origin of the event generation is concerned. This information about the location can also be used in many network applications like routing, path finding and load balancing etc. Many location estimation techniques have been suggested by many researchers but most of them are carried out in the constrained environment. In this paper different localization approaches have been discussed. This paper also provides an overview of different schemes proposed for localization improvement. The future challenges in the localization are also discussed.